4th report on the world nutrition situation: nutrition throughout the life cycle - United Nations, Administrative Committee on Coordination, Subcommittee on Nutrition; International Food Policy Research Institute (United Nations, 2000)
The Fourth Report on the World Nutrition Situation is part of a series of ACC/SCN reports initiated in the mid- 1980s on the nutritional status of populations in developing countries....This report is built around the theme 'nutrition throughout the life cycle'...This report highlights the size of the malnutrition problem and its consequences for human and economic development. It stresses the need to move ahead in creative partnerships. The Fourth Report provides evidence of contrasts — contrasts in the prevalence and trends of malnutrition, contrasts in actions taken, contrasts in progress made, and contrasts in the availability of data on the extent and causes of malnutrition." (Forward by Richard Jolly and Per Pinstrup-Andersen)